Regulatory T cells and immune escape in HCC: understanding the tumor microenvironment and advancing CAR-T cell therapy - Du, Guangtan; Dou, Cunmiao; Sun, Peng; Wang, Shasha; Liu, Jia; Ma, Leina (Frontiers in Immunology, 2024)
Liver cancer, which most commonly manifests as hepatocellular carcinoma (HCC), is the sixth most common cancer in the world. In HCC, the immune system plays a crucial role in the growth and proliferation of tumor cells. HCC achieve immune escape through the tumor microenvironment, which significantly promotes the development of this cancer. Here, this article introduces and summarizes the functions and effects of regulatory T cells (Tregs) in the tumor microenvironment, highlighting how Tregs inhibit and regulate the functions of immune and tumor cells, cytokines, ligands and receptors, etc, thereby promoting tumor immune escape. In addition, it discusses the mechanism of CAR-T therapy for HCC and elaborate on the relationship between CAR-T and Tregs.